Analisis Transparansi dan Akuntabilitas Pengelolaan Dana Sekolah - Heliani; Wahidin, Dede; Susilawati, Erma (Jurnal Aktiva : Riset Akuntansi dan Keuangan, 2020)
This study, entitled the analysis of transparency and accountability in the management of school funds at SMK Plus Nusa Putra. The objectives of this study are: 1) to determine the description of school fund management 2) to find out whether the school has implemented transparency and accountability completely 3) to determine how the implementation of transparency in SMK Plus Nusa Puta. The method used in this research is descriptive qualitative method, how to collect data using direct interviews and data on BOS fund receipts at SMK Plus Nusa Putra. The results of the study indicate that the transparency of fund management at SMK Plus Nusa Putra leads to the transparent category.